Comorbidities and quality of life in children with intellectual disability - Reddihough, D.; Leonard, H.; Jacoby, P.; Kim, R.; Epstein, A.; Murphy, N.; Reid, S.; Whitehouse, A.; Williams, K.; Downs, Jennepher (WILEY, 2021)
Background: Many children with intellectual disability live with medical comorbidities. This study examined the impacts of comorbidities on quality of life (QOL) of children with intellectual disabilities and whether impacts varied with caregiver perceptions that medical needs had been met.